Mothers’ Breastfeeding Practices and Self-Efficacy - Agrina Agrina; Febriana Sabrian; Oswati Hasanah; Erika Erika; Yesi Hasneli (Jurnal Keperawatan Indonesia, 2021)
This study examined breastfeeding practices and self-efficacy among mothers residing in rural areas. A cross-sectional study was conducted for 104 mothers via purposeful sampling in a Posyandu (maternal and child health service) in Kampar district, one of the rural areas in Riau, Indonesia. The Breastfeeding Self-Efficacy Scale Short Form (BSES-SF) was used in the questionnaires to collect data. Chi-square test was used for bivariate analysis. Majority of the respondents (71.2%) were 20–35 years old; 69.3% of the respondents’ level of education were low (such as junior and senior high school levels). Approximately 91.3% of them were housewives. Exclusive breastfeeding prevalence was only 30.8%, with insufficient milk being the most common reasons cited by the mothers as failure to breastfeed exclusively. Porridge and mineral water were the most commonly supplied food given to babies under 6 months among 31.7% and 36.5% mothers, respectively. The respondents faced some breast problems, where 72.1% mothers did not have good breastfeeding skills. Approximately 59.6% mothers had higher breastfeeding self-efficacy than the mean score for BSES-SF, which was 58.58 (11.58 standard deviation [SD]). Mothers’ age was significantly correlated with the BSES among mothers (p < 0.01). Increasing young mother’s breastfeeding self-efficacy during the antenatal care period is important to lower these young mothers’ perception of having insufficient milk. Abstrak Praktik Menyusui dan Efikasi Diri Ibu. Penelitian ini bertujuan untuk menggambarkan tentang praktik pemberian air susu ibu (ASI) dan efikasi diri ibu menyusui di daerah pedesaan. Penelitian ini menggunakan pendekatan cross sectional pada 104 ibu yang berkunjung ke Posyandu sebagai tempat pos kesehatan untuk ibu dan anak yang diambil menggunakan teknik purposeful sampling. Alat penggumpulan data menggunakan kuisioner breastfeeding self-efficacy Scale Short Form (BSES -SF) yang telah valid dan realiabel pada penelitian sebelumnya. Analisis Chi square digunakan pada analisa bivariate. Mayoritas usia responden adalah berada pada rentang 20-35 tahun (71,2%) dengan pendidikan yang terbanyak adalah sekolah menengah pertama dan atas (69,3%). Hampir seluruh responden tidak memiliki pekerjaan diluar rumah (91,3%). Hanya 30,8% ibu memberikan ASI saja dengan alasan utama ASI yang tidak cukup sebagai alasan utama. Sebagai alternatif maka ibu memberikan bubur dan air putih sebagai makanan utama kepada bayi sebelum berusia 6 bulan. Kebanyakan ibu mengalami masalah dalam menyusui dan hanya 27,9% ibu memiliki kemampuan yang tepat dalam menyusui. 59,6% efikasi diri ibu menyusui di atas mean efikasi diri responden (58,58, SD 11,58). Usia ibu signifikan berhubungan dengan efikasi diri ibu menyusui (p< 0,01). Perlu ditingkatkan efikasi diri pada ibu muda selama masa kehamilan agar persepsi ibu tentang kecukupan ASI menjadi lebih baik. Kata Kunci: efikasi diri, ibu, praktik nenyusui